(Main)streaming English Dubs: A Snapshot of Netflix’s Playbook on Dubbing Strategies - Hayes, Lydia; Bolaños-García-Escribano, Alejandro (Journal of Audiovisual Translation, 2022)
With ‘original’ content from a growing diversity of languages, Netflix has become a playground for audiovisual translation. Given that Netflix outsources its localisation, it has been able to rely on practitioners in consolidated industries to create revoiced and subtitled versions that adhere to industry conventions. Although subtitling has long been the consolidated mode for localising mainstream audiovisual products (films and series) into English, Netflix has initiated new trends in an Anglophone dubbing industry traditionally reserved for niche products, by bringing the dubbing of foreign-language mainstream products into the distribution mainstream. The illusory novelty of English dubs, debuted at the turn of 2017 on Netflix, has facilitated experimentation in dubbing strategies. In the burgeoning English-dubbing industries, located mainly in Los Angeles and London, standardisation, domestication and foreignisation strategies are being used (Hayes 2021; 2022). In order to elucidate emerging norms in English-dubbing strategies, in this article we present a corpus of Netflix’s English dubs of 82 Castilian-Spanish films and TV series and analyse the main dubbing strategies adopted by the studios involved. Lay summary Netflix has original series and films in many languages and the need to translate these into other languages has led to Netflix experimenting with different ways of translating content, such as by creating subtitles or dubbed versions (replacing the original dialogues with voices speaking another language). For importing “foreign” content (e.g. Spanish productions) into the English language, subtitling has traditionally been the mode of translation used for films and series, but dubbing has also been used for products such as cartoons and videogames. As Netflix outsources translation, they have been able to rely on professionals in well-established translation industries; however, in the case of translating into English, dubbing live-action has generally presented a new challenge for English-language translation professionals. Furthermore, most viewers of English dubs were previously unfamiliar with dubbing. Therefore, experimentation in English-dubbing strategies has been possible. Netflix’s English dubs utilise different accents (e.g. standard, regional or foreign) depending on different variables, such as the country where the dubbed version was created or the dubbing director. In this article, we have analysed 82 Spanish films and series on Netflix and their English dubs, in order to determine the presence different accent strategies and developing trends. The films and series studied were released on Netflix between 2017 and 2021 and were available on the platform in Ireland and UK throughout 2021. We ultimately draw conclusions that reveal our observations on current practices in English-language dubbing.